Literacy lessons for a digital world : using blogs, wikis, podcasts, and more to meet the demands of the Common Core - Diamond, Jamie E.; Gaier, Meg C. (New York : Scholastic, 2014)
A language arts and math teacher have teamed together to create technology-rich lessons that teach the key literacy skills and strategies demanded by the CCSS in a highly motivating way. Use digital storytelling to retell myths, go on a geometry scavenger hunt, create a travel "commercial" for a historical place, and so much more. Tap into the power of wikis to facilitate literature discussions, build background knowledge with inquiry circles in science, collect practical applications of math concepts, present research on history topics--and that's just the beginning! With model lessons and dozens of lesson ideas for every content area, how-to's for getting started with the technology, assessment tips, and student samples on the enclosed CD, you'll find everything you need to teach with technology today! For use with Grades 5 & Up.
1. Digital storytelling -- 2. Blogs -- 3. Wikis -- 4. Podcasts.
System requirements for accompanying CD-ROM: computer with disc drive, PDF reader, sound and video players.
"Grades 5 and up"--Title page.
"Includes CD"--Front cover.
"CCSS, supports the Common Core State Standards"--Front cover.
Accompanying disc contains, videos, podcasts and PDF files.
Includes bibliographical references (page 144).
Keywords: Education -- Data processing; Computer-assisted instruction